2014
DOI: 10.1112/jlms/jdu056
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-reflection groups and essential dimension

Abstract: We give a simple formula for the essential dimension of a finite pseudo-reflection group at a prime p and determine the absolute essential dimension for most irreducible pseudo-reflection groups. We also study the 'poor man's essential dimension' of an arbitrary finite group, an intermediate notion between the absolute essential dimension and the essential dimension at a prime p.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…• Alexander Duncan and Zinovy Reichstein observed that Theorem 1.6 can be used to extend Theorem 1.4 of their article [DR14] to the case of an arbitrary ground field k; originally they proved it only over an infinite k. Their theorem compares variants of the notion of essential dimension for finite subgroups of GL n (k). Here is another application, in the same spirit as [DR14, Theorem 8.1].…”
Section: Applicationsmentioning
confidence: 99%
“…• Alexander Duncan and Zinovy Reichstein observed that Theorem 1.6 can be used to extend Theorem 1.4 of their article [DR14] to the case of an arbitrary ground field k; originally they proved it only over an infinite k. Their theorem compares variants of the notion of essential dimension for finite subgroups of GL n (k). Here is another application, in the same spirit as [DR14, Theorem 8.1].…”
Section: Applicationsmentioning
confidence: 99%
“…Let W (E 6 ) act on h via the defining representation, and let A(h) denote the corresponding faithful linear W (E 6 )-variety. Then by [DuRe2,Lemma 6.1]…”
Section: Finding a Single Linementioning
confidence: 99%
“…To see this, we need the following Bertini-type result which asserts the existence of general hypersurface sections containing a given closed subvariety. See [22,Theorem 1] or [10,Theorem 8.1] for a similar treatment. For the convenience of the reader, here we give its proof.…”
Section: Weak Numerical Equivalencesmentioning
confidence: 99%